Leave only footprints : my Acadia-to-Zion journey through every national park - Knighton, Conor (Crown, an imprint of Random House, 2020)
"The Emmy-winning CBS Sunday Morning correspondent chronicles his year traveling to every one of our National Parks, discovering the most beautiful places and most interesting people that America has to offer. When Conor Knighton decided to spend a year wandering through America's "best idea," he was worried the whole thing might end up being his worst idea. But after a broken engagement and a broken heart, Conor desperately needed a change of scenery. The ambitious plan he cooked up went a bit overboard in that department; Knighton set out to visit every single one of America's National Parks, from Acadia to Zion. Leave Only Footprints is the memoir of his year spent traveling across the United States, a journey that yielded his "On the Trail" series, which quickly became one of CBS Sunday Morning's most beloved segments. In this smart, informative, and entertaining book, he shares how his journey through these natural wonders ended up changing his worldview on everything from God and love to politics and technology. Whether he's waking up early for a naked scrub in a historic bathhouse or staying up late to stargaze along our loneliest highway, Knighton goes behind the scenery to provide an unfiltered look at our country. In doing so, he reveals the unforgettable stories behind the often beautiful, always fascinating lands that all Americans share"--